FORMULATION AND INVITRO EVALUATION OF ATAZANAVIR ORAL DISINTEGRATING TABLETS - ARCHANA, G.; RAJU, P. NARAYANA; REDDY, G. NAGARJUNA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: In this present work oral disintegrating tablet of atazanavir were designed with a view to avoid the first pass effect and to improve the bioavailability of atazanavir. Method: Total fifteen formulations were prepared using superdisintegrants like cross povidone, cross carmellose sodium and sodium starch glycolate at concentrations 5 – 15 %. For better mouth feel sweetening agents and flavouring agents were added. Oral disintegrating tablet of atazanavir were prepared by direct compression method. Results: The prepared powdered blend of the formulations were evaluated for micromeritic properties like angle of repose, bulk density, tapped density, Hausner's ratio, Carr's compressibility index and results showed that the powder blend has good flow property. The prepared batches of tablets were evaluated for post compression parameters like weight variation, content uniformity, thickness, hardness, wetting time, in vitro disintegrating time and friability and the results were found to be uniform within the pharmacopoeial limits. Effect of superdisintegrants on in-vitro release of drug has been studied. Among the 15 formulations tablet containing cross povidone (15%) showed excellent in-vitro disintegration time of 21 secs and complete drug release in 15 mins. FTIR & DSC studies confirmed that there is no evidence of interaction between the drug and superdisintegrants and the selected ingredients were compatible. Conclusion: It is concluded that oral disintegrating atazanavir tablets could be prepared by direct compression using different concentration of superdisintegrants. Keywords: Atazanavir, superdisintegrants, direct compression, oro disintegrating tablets.